2007
DOI: 10.1002/ca.20556
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic variation of the spinal origins of lateral and medial pectoral nerves

Abstract: Lateral and medial pectoral nerves are distributed to the pectoralis major and minor muscles. The purpose of this study was to identify the spinal origins of lateral and medial pectoral nerves and to evaluate the participating amounts of each spinal nerve composing both pectoral nerves. Two types of spinal origins appeared in lateral pectoral nerves. The first type was composed of nerve fibers from C5, C6, and C7 with a frequency of 50.0% and the second type was composed of nerve fibers from C6 and C7 at a fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…In a cadaveric dissection study [2,7], It was reported that, the lateral pectoral nerve arises most frequently with two branches from the anterior divisions of the upper & middle trunks (33.8%) or as a single root from the lateral cord (23.4%) & the medial pectoral nerve usually arises from the medial cord (49.3%), from anterior division of the lower trunk (43.8%), or from the lower trunk (4.7%). They found that 02 pectoral nerves are usually connected immediately distal to the thoracoacromial artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cadaveric dissection study [2,7], It was reported that, the lateral pectoral nerve arises most frequently with two branches from the anterior divisions of the upper & middle trunks (33.8%) or as a single root from the lateral cord (23.4%) & the medial pectoral nerve usually arises from the medial cord (49.3%), from anterior division of the lower trunk (43.8%), or from the lower trunk (4.7%). They found that 02 pectoral nerves are usually connected immediately distal to the thoracoacromial artery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the surgeons are supposed to have thorough knowledge about the anatomy of the medial and lateral pectoral nerves and its possible variations to prevent and to minimise the possible complications due to injury to these nerves (denervation) [2]. Even cosmetic surgeons also deal with these nerves during breast augmentations (breast implants) for the females who desire to have better projection and attractive contour for their breasts [3].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of variations of pectoral nerves is also important for plastic surgeons and head and neck surgeons because pectoral nerve denervation may be helpful in decreasing the pain and spasm in the head and neck surgery and also the pectoralis major myocutaneous flap is one of the most frequently used flaps in head and neck reconstruction [8]. The lateral pectoral nerve may arise from the lateral cord or from the anterior divisions of the upper and middle trunks [9]. Gupta et al, [10] have reported the origin of two lateral pectoral nerves as two separate branches from the anterior divisions of upper and middle trunks.Its origin from the posterior division of the upper trunk has been reported by Singhal et al, [11].…”
Section: Discussionmentioning
confidence: 99%
“…Three main spinal origin configurations exist for the MPN (see Fig. 2) [10]. However, 73% are composed of fibers from C8 and T1, alternatively C8 alone or T1 alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this hypothesis, we also expected to see a generalized trend towards improved outcome in patients who underwent surgery sooner (less than 6 months post-injury) than later, and patients having direct MPN-AXN neurotization. However, we were not [10] able to do a formal statistical analysis in these parameters as the patient enrollment in this case series was relatively small (n=8).…”
Section: Discussionmentioning
confidence: 99%